Gross Morphological study on Scapula of Mithun (Bos frontalis) - Malsawmkima; Imtiwati; Laltlankimi; Lalsangpuii (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted on scapula of adult mithun to study the gross morphological anatomy and record certain biometrical measurements. The bones were procured by simple natural maceration process. The scapula of mithun was found to be a flat triangular bone having three angles, three borders and two surfaces. The dorsal border was convex and the scapular spine was found to be thickened and roughened at the middle and then bend/curved forward below and ended distally as a pointed projection, acromion process. The rim of glenoid cavity was found to be roughly quadrilateral in outline and presented a wide and a narrow notch at the lateral and cranio-medial aspect of the glenoid cavity, respectively. The average maximum length and width of the scapula were found to be 35.87±0.43 cm and 20.85±0.75 cm, respectively.